1994
DOI: 10.1159/000201174
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Activities of Agonists of Active Duodenal Bicarbonate Secretion in the Guinea Pig

Abstract: The comparative activity of agonists of duodenal bicarbonate secretion was studied in the anesthetized guinea pig, where the duodenal lumen was perfused with 24 mmol/l NaHCO3 to ensure active secretion of bicarbonate. Agonists were infused alone and in combination. Dibutyryl 3’,5’-cyclic adenosine monophosphate, vasoactive intestinal polypeptide (VIP) and prostaglandin E2 (PGE2) were strong stimulants of bicarbonate secretion. Theophylline, dibutyryl 3’,5’-cyclic guanosine mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Aliquots of 0.5 mL were removed, 5 μ L of 10% BSA was added, and the mixture was incubated in a shaking water bath at 37 °C for exactly 2 min, then 5 μ L of PBS (for basal determination of cAMP) or 5 μ L of VIP was added to the incubation solution. This gave a final concentration of 5 × 10 −7 m for VIP, corresponding to doses having maximum stimulatory effect on duodenal HCO secretion in our studies with the anaesthetized guinea‐pig (Odes et al. 1994, Reimer et al.…”
Section: Intracellular Camp Generationmentioning
confidence: 98%
“…Aliquots of 0.5 mL were removed, 5 μ L of 10% BSA was added, and the mixture was incubated in a shaking water bath at 37 °C for exactly 2 min, then 5 μ L of PBS (for basal determination of cAMP) or 5 μ L of VIP was added to the incubation solution. This gave a final concentration of 5 × 10 −7 m for VIP, corresponding to doses having maximum stimulatory effect on duodenal HCO secretion in our studies with the anaesthetized guinea‐pig (Odes et al. 1994, Reimer et al.…”
Section: Intracellular Camp Generationmentioning
confidence: 98%
“…In mice and rats mRNA for the PGE 2 receptor subtypes EP2R and EP4R has been detected in the intestinal mucosal layer 910PGE 2 was previously shown to stimulate adenylate cyclase in rat intestinal epithelial cells via a receptor mediated mechanism,11 and to enhance bicarbonate secretion in guinea pig intestine 12. The mRNA expression of G s linked EP2R and EP4R,10 the observed activation of adenylate cyclase by PGE 2 ,11 and the reported stimulation of 3- O -methylglucose uptake by dbcAMP4 in enterocytes suggested that PGE 2 should enhance intestinal glucose absorption.…”
mentioning
confidence: 99%
“…It is possible that the neural mechanisms involved in VIP-stimulated secretion may be suppressed by NKA. Alternatively, PGE 2 , which we believe to be released by NKA, may decrease VIP-stimulated alkaline secretion as has been shown in guinea pigs (24). Furthermore, the notion that VIPstimulated duodenal secretion of bicarbonate may be negatively modulated by prostaglandins is supported by the finding that the effect of VIP on luminal alkalinization is potentiated by indomethacin (35).…”
Section: Bicarbonate Secretionmentioning
confidence: 61%